ON BEING MUSLIM AMERICANS: MIPSTERZ AS A SITE FOR NEGOTIATING IDENTITY - Chusna, Aidatul; Riyanti, Erni Dewi (Indonesian Journal of Interdisciplinary Islamic Studies (IJIIS), 2020)
The arrival of immigrants from various countries and continents to America has become part of a very long history for this country. In fact, the United States was founded by group of immigrants. History accounts the arrival of Muslim immigrants in America in several waves; nonetheless, Islam and Muslims remained foreign for American people. For Muslim Immigrants, the tragedy of September 11 (2001) had profoundly impacted them. They endure prejudices, discrimination, verbal abuse, and hate crimes due to the increasing Islamophobia among American society. The study highlights a group of young Muslims known as Mipsterz (Muslim Hipsters) and examines how Mipsterz becomes a site for negotiating identity as a Muslim American. Started as a small group of Muslim youngsters from New York City in 2012, Mipsterz develops into a space for minorities to speak up and define themselves through their creative works. Unluckily, along with the growing number of white supremacists, Islamophobia and negative stereotypes are keep growing and felt by Muslim Americans, even among American-born Muslim generations. Mipsterz aims to keep producing stories and marginalized voices to the fore front of American public, as its members do not want to be identified either Muslims or Americans; they are Muslim Americans.